(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
Lukoil has invested billions of dollars in its projects in Uzbekistan, and a significant part of the gas produced is exported. At the same time, the company also contributes to social projects, charity work and infrastructure development.